Three‐Dimensional Transesophageal Echocardiographic Study of Aortic‐Mitral Valve Coupling after Coronary Artery Bypass Grafting. Issue 6 (23rd September 2014) - Qu, Shao‐Hui; Hsiung, Ming‐Chon; Leng, Xiao‐Ping; Wei, Jeng; Du, Guo‐Qing; Houle, Helene; Yin, Wei‐Hsian; Tian, Jia‐Wei
<x xml:space="preserve">Abstract</x> Aims To observe the geometric changes in aortic‐mitral valve coupling (AMC) on three‐dimensional transesophageal echocardiography and the factors leading to decreased mitral regurgitation (MR) after coronary artery bypass grafting (CABG). Methods and Results This study included 23 patients undergoing CABG for coronary artery disease. Fifteen patients with moderate to severe MR were separately analyzed to determine whether the severity of MR influences the geometric change in AMC. Echocardiographic examinations were performed pre‐ and post‐CABG, and the studied parameters were obtained using Siemens Auto Valve Analysis software. The effective mitral regurgitant orifice area, left ventricular ejection fraction (LVEF), end‐diastolic volume (EDV), and end‐systolic volume (ESV) were measured pre‐ and post‐CABG using Philips QLAB software. Ischemic MR, EDV, and ESV significantly decreased (all P < 0.05) and LVEF significantly improved (P < 0.05) after CABG. There were no significant differences between the pre‐ and post‐CABG mitral valve (MV) parameters, aortic valve parameters, aortic‐mitral annular angle, or centroid distance (all P > 0.05). Patients with moderate to severe MR exhibited the same results. Conclusion The results of this study show that CABG does not cause an acute change in the geometry of AMC. Improved left ventricular function might increase the closing force of the MV, leading to decreased MR after CABG alone. MR significantly improved after CABG alone without MV treatment in the present study. This result may help to guide surgeons in choosing the optimal surgical methods for individual patients.